'Irreversible': The Role of Digitization to Repurpose State Records of Repression. (25th January 2019) - Guberek, Tamy; Muralles, Velia; Alpert-Abrams, Hannah
ABSTRACT∞ : Since mid-2005, archivist–activists at the Historical Archive of the National Police of Guatemala have been digitizing a century's worth of previously suppressed police records so as to protect, mobilize and provide access to them – 23 million pages to date. We find that digitization amplified the staff's repurposing of the archive to serve victims of human rights violations. Digitization enhances short- and long-term safeguards for the archive's physical integrity, probative value and enduring accessibility, but has required critical human factors and institutional solidarity, most notably partnerships with international donors and allied organizations, and Guatemalan nongovernmental organizations. Finally, technology offers a lens to analyze the persistent challenges to promoting truth and justice in Guatemala. We show how simple, often ad hoc approaches to digitization developed under political urgency can have an irreversible impact when used to amplify a unified mission driven by a committed community of archival workers.